A [3+2] cycloaddition-1, 2-acyl migration-hydrolysis cascade for regioselective synthesis of 1, 2, 3-triazoles in water. Issue 64 (21st July 2021) - Chakraborti, Gargi; Mandal, Tirtha; Roy, Charles Patriot; Dash, Jyotirmayee
Abstract : A [3+2] cycloaddition, 1, 2-acyl migration and hydrolysis cascade is delineated for the synthesis of 2 H -1, 2, 3-triazoles via the regioselective formation of N 2 -carboxyalkylated triazoles using a prolinamide ligand in water. Abstract : A cascade sequence involving [3+2] cycloaddition, 1, 2-acyl migration and hydrolysis produces 2 H -1, 2, 3-triazoles via the regioselective formation of N 2 -carboxyalkylated triazoles. The reaction proceeds in aqueous media through intriguing reaction kinetics using a CuI–prolinamide catalyst system. Prolinamide promotes the novel organocatalytic 1, 2-acyl migration as well as hydrolysis of the resulting N 2 -carboxyalkylated triazoles.